Mechanism of Yanghe Pingchuan granules treatment for airway remodeling in asthma - Pan LY; Han YQ; Wang YZ; Chen QQ; Wu Y; Sun Y (Dove Medical Press, 2018)
LingYu Pan,1,* YanQuan Han,1,* YongZhong Wang,1 QianQian Chen,2 Ying Wu,2 Yuan Sun2 1Grade 3 Preparation Laboratory of State Administration of TCM, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui 230031, China; 2Anhui University of Chinese Medicine, Hefei, Anhui 230031, China *These authors contributed equally to this work Purpose: Yanghe Pingchuan granules (YPG), a hospital preparation developed by The First Affiliated Hospital, Anhui University of Chinese Medicine, has been used for the clinical treatment of bronchial asthma (BA) for several decades. This study aimed to explore the mechanism of action of YPG in the treatment of BA. Materials and methods: Male Sprague Dawley rats (n=60) were randomly divided into six groups (n=10 per group): control, a BA model, positive drug control (Guilong Kechuanning capsules; a proven effective treatment for BA), and model rats treated with a high, medium, or low dose of YPG. H&E staining was used to detect pathological changes in the bronchial tubes. The mRNA expression levels of PI3K, PKB, PCNA, and AR were determined by real-time PCR, and the protein levels of phospho- (p-)PI3K, p-PKB, p-PCNA, and p-AR were detected by Western blotting. ELISAs were used to detect the expression of PIP2, PIP3 IL-6, IL-8, IL-1β, and epinephrine (EPI). Results: H&E staining demonstrated that BA can be ameliorated using YPG. Real-time PCR, Western blotting, and ELISA indicated that use of YPG decreased expression of the phosphoinositide 3-kinase (PI3K) signaling pathway and PCNA, and can also ameliorate the condition kidney Yang deficiency, which is associated with BA in Chinese traditional medicine. Conclusion: YPG can attenuate BA therapeutically in a dose-dependent manner. The mechanism underlying its therapeutic effect comprises influences on three features that contribute to BA: the PI3K signaling pathway, cell proliferation, and “kidney-Yang deficiency”. Keywords: bronchial asthma, YPG, PI3K/PKB signaling pathway, cell proliferation, kidney Yang deficiency